Pengaruh Pembelajaran Berbasis Google Classroom Terhadap Hasil Belajar PJOK - Sarifudin Sarifudin; Sholeh Hidayat; Lukman Nulhakim (Universitas Mathla'ul Anwar Banten, 2022)
The development of information technology and multimedia is so rapid that we are not ready to make full use of it. Learning models need to be well designed so that the student's learning experience is memorable and can achieve learning. The learning model is also important because it is used by teachers as a guide in planning and implementing teaching and learning activities. The COVID-19 pandemic has made preventive prevention services closed by closing schools that are in the Covid-19 red zone. One way teachers can continue to provide learning to students is online or online. However, the implementation of the online learning process has several obstacles. In addition, problems that are often encountered in learning physical education, sports and health (PJOK) in schools are the low interest and learning activities of students so that student learning outcomes are less than optimal. To overcome learning obstacles during the COVID-19 pandemic, Google Classroom-based bold learning media is used so that student learning outcomes can increase. This study uses an experimental method with an experimental class and a control class, with the results of student learning outcomes using google classroom higher than students who do not use google classroom.